2007
DOI: 10.1016/j.abb.2006.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the cutaneous synthesis and dietary sources of vitamin D

Abstract: The major sources of vitamin D for most humans are casual exposure of the skin to solar ultraviolet B (UVB;290-315 nm) radiation and from dietary intake. The cutaneous synthesis of vitamin D is a function of skin pigmentation and of the solar zenith angle which depends on latitude, season, and time of day. In order to mimic the natural environment of skin to sunlight exposure, we therefore measured serum 25-hydroxyvitamin D levels in volunteers with different skin types following repeated UV irradiation. Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
394
2
19

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(428 citation statements)
references
References 25 publications
13
394
2
19
Order By: Relevance
“…While previous studies have identified foods containing vitamin D as predictors of serum 25(OH)D concentration following the winter (6)(7)(8) , particularly milk (24,25) , we did not find any association with dietary sources of vitamin D. Because the vitamin D content of most foods is low relative to the amount produced in skin (5) , we may not have been able to detect the relatively small contribution of diet. Skin type, another factor known to be associated with vitamin D status, was not associated with serum 25(OH)D concentration in our study likely because of the lack of variation in this factor as almost all women in our study were white.…”
Section: Discussioncontrasting
confidence: 89%
“…While previous studies have identified foods containing vitamin D as predictors of serum 25(OH)D concentration following the winter (6)(7)(8) , particularly milk (24,25) , we did not find any association with dietary sources of vitamin D. Because the vitamin D content of most foods is low relative to the amount produced in skin (5) , we may not have been able to detect the relatively small contribution of diet. Skin type, another factor known to be associated with vitamin D status, was not associated with serum 25(OH)D concentration in our study likely because of the lack of variation in this factor as almost all women in our study were white.…”
Section: Discussioncontrasting
confidence: 89%
“…The vitamin D within the same food products may also vary, with recent research showing that the vitamin D content of fish may vary enormously depending on whether fish is farmed or wild. For instance, Chen et al (33) analysed the vitamin D content of both wild and farmed salmon and discovered that wild salmon contained four times the vitamin D content of farmed salmon. Despite the relatively low amount of dietary vitamin D found naturally in foods, there is a growing interest in the role of vitamin D-fortified foods and supplements in improving vitamin D status.…”
Section: Vitamin D Food Sourcesmentioning
confidence: 99%
“…The potential for pre-vitamin D 3 production is reduced further still by dark skin pigmentation. Other things being equal, the higher the eumelanin content, the lower the rate of previtamin D 3 production in the skin [2,20,21,[27][28][29][30][31][32][33][34][35][36][37][38]. When the zones of cutaneous pre-vitamin D 3 production potential are mapped following a previously established protocol [2], it is evident that lightly pigmented people inhabiting the zone near the equator can experience enough UVB through casual sun exposure on unprotected skin to produce physiologically adequate amounts of vitamin D. In the subtropical zone, there is at least one month during which there is insufficient UVB to catalyse pre-vitamin D 3 production for people with lightly pigmented skin, and during which they must rely on stored vitamin D (as 25-hydroxyvitamin D; 25(OH)D) to satisfy their physiological needs.…”
Section: Human Exposure To Ultraviolet Radiationmentioning
confidence: 99%